Criss-Cross Times : Selected Writings About Conflict and Confluence, 2001-2009 - Javed, Jabbar (Karachi Royal Book Company, 2010)
Selected writings and observations on conflict and confluence between 2001 and 2009 on international, national affairs and on media.
Keywords: Mass Media -- Pakistan -- Politics and government -